Economia solidária e economia da cultura em Foz do Iguaçu: estudo de caso do Ponto de Cultura Maracatu Alvorada Nova - Winkert, Sérgio Luiz (2018)
The capitalist mode of production in the face of all its complexity represents an economic system that encourages competitiveness and promotes inequality. The workers face changes in labor relations or even the extinction of these, as a decrease in jobs due to the Industrial Revolution III or the precariousness of labor itself. In this context, elements such as cooperation, solidarity through self-management and economic action, principles of solidarity economy, arise as opportunities for work and income. The research has as its main axis the foundations of Solidarity Economy (ECOSOL) and its importance in the development of the Culture Economy in Foz do Iguaçu. For this, Maracatu Alvorada Nova, the first Maracatu of Foz do Iguaçu, was chosen as the object of study. Through an exploratory, bibliographical, documentary and field study research. A historical contextualization of the origin and the evolutionary process of the Maracatu Group will be presented in the case study format. This will verify the importance or relevance of applying the ECOSOL principles to the organizational evolution of this cultural initiative, as well as the relationships and articulations used to strengthen this solidarity enterprise.